KONDISI EKOLOGI MANGROVE DI KAMPUNG SENTOSA BARAT KELURAHAN BELAWAN SICANANG KECAMATAN MEDAN BELAWAN (The Ecological Condition of Mangrove in West Sentosa Village, Belawan Sicanang, Medan Belawan District) - Ely Ermayani; Yunasfi Djayus; Zulham Apandy Harahap (AQUACOASTMARINE, 2016)
Mangrove is the living plant community between the sea and the land that was influenced by the tides. West Sentosa Village still has a natural mangrove ecosystem. But, mangrove in West Sentosa Village has long been used by the local community as a source of livelihood especially mangrove forest logging for aquaculture. This research aimed to know the ecological condition, condition of the mangrove waters and gastropod diversity associated with mangrove vegetation. This research is done in February until April 2016. Methode of the research is Purposive Random Sampling method by taking and observing of biotic components which was mangrove vegetation and density of gastropods and the measurement of water quality parameters. There are 11 kinds of mangrove which found in the research location, namely Acrostichum speciuosum, Avicennia alba, Avicennia marina, Bruguiera sexangula, Excoearia agallocha, Lumnitzera littorea, Nypa fruticans, Rhizophora apiculata, Rhizophora stylosa, Sonneratia caseolaris dan Sonneratia ovata. The kinds of mangrove substarate at this research are silty loam, clay loam and sand loam.Keywords : gastropod, mangrove, substrate, the ecological condition, water quality